Shaping Synapses by the Neural Extracellular Matrix - Ferrer-Ferrer, Maura; Dityatev, Alexander (Frontiers in Neuroanatomy, 2018)
Accumulating data support the importance of interactions between pre- and postsynaptic neuronal elements with astroglial processes and extracellular matrix (ECM) for formation and plasticity of chemical synapses, and thus validate the concept of a tetrapartite synapse. Here we outline the major mechanisms driving: (i) synaptogenesis by secreted extracellular scaffolding molecules, like thrombospondins (TSPs), neuronal pentraxins (NPs) and cerebellins, which respectively promote presynaptic, postsynaptic differentiation or both; (ii) maturation of synapses via reelin and integrin ligands-mediated signaling; and (iii) regulation of synaptic plasticity by ECM-dependent control of induction and consolidation of new synaptic configurations. Particularly, we focused on potential importance of activity-dependent concerted activation of multiple extracellular proteases, such as ADAMTS4/5/15, MMP9 and neurotrypsin, for permissive and instructive events in synaptic remodeling through localized degradation of perisynaptic ECM and generation of proteolytic fragments as inducers of synaptic plasticity.